The impact of the West Sumatran regional recording industry on Minangkabau oral literature - Suryadi, S. (UI Scholars Hub, 2010)
Due to the emergence of what in Indonesian is called industri rekaman daerah 'Indonesian regional recording industries', which has developed significantly since the 1980s, many regional recording companies have been established in Indonesia. As a consequence, more and more aspects of Indonesian regional culture have appeared in commercial recordings. Nowadays commercial cassettes and Video Compact Discs (VCDs) of regional pop and oral literature genres from different ethnic groups are being produced and distributed in provincial and regency towns, even those situated far from the Indonesian capital of Jakarta. Considering the extensive mediation and commodification of ethnic cultures in Indonesia, this paper investigates the impact of the rise of a regional recording industry on Minangkabau oral literature in West Sumatra. Focussing on recordings of some Minangkabau traditional verbal art genres on commercial cassettes and VCDs by West Sumatran recording companies, this paper attempts to examine the way in which Minangkabau traditional verbal art performers have engaged with electronic communication, and how this shapes technological and commercial conditions for ethnic art and performance in one modernizing society in regional Indonesia.